Pengaruh Kecerdasan Emosional Dan Potensi Kewirausahaan Terhadap Keberhasilan Berwirausaha : Studi Terhadap Wirausaha Etnis Toraja di Kota Ambon - Dessy Balik (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2020)
The purpose of this study was to conduct empirical evidence of the influence of emotional intelligence and entrepreneurial potential on the success of the Toraja Ethnic entrepreneurship. This type of research is an exsplanatory study, the analytical approach in research is quantitative research, model of this research is survey research. The unit of analysis in this study is the Toraja Ethnic entrepreneur who has a business activity in Ambon City. Time horizon of one stage research (cross sectional), data collection using survey methods using questionnaire instruments. Determination of the sample using non-probability sampling methods, sample selection in this study uses judgment sampling sampling techniques. The sampling criteria are as follows: 1) Respondents are Toraja Ethnic entrepreneurs, 2) Respondents are Toraja Ethnic entrepreneurs who carry out micro, small and medium-scale business activities in the Ambon City area for a minimum of 5 years. 3) Respondents are ethnic Toraja entrepreneurs who conduct business activities independently, or not in the form of joint ventures. The type of data in this study is primary data. The number of samples analyzed in this study 160 sample units. Data analysis techniques used inferential statistical analysis (multiple regression). The results of multiple linear regression analysis prove that emotional intelligence and entrepreneurial potential have a positive effect on the success of ethnic Toraja entrepreneurship in Ambon City. The results of this study explain the relationship of emotional intelligence with entrepreneurial potential as a combination of psychological aspects of entrepreneur and entrepreneurial aspects that are determinants of entrepreneurial success. Keywords: emotional intelligence, entrepreneurial potential, entrepreneurial success.